Chemical Constituents of Essential Oils Used in Olfactory Training: Focus on COVID-19 Induced Olfactory Dysfunction - Koyama, Sachiko; Heinbockel, Thomas (Frontiers in Pharmacology, 2022)
The recent increase in the number of patients with post-viral olfactory dysfunction (PVOD) following the outbreak of COVID-19 has raised the general interest in and concern about olfactory dysfunction. At present, no clear method of treatment for PVOD has been established. Currently the most well-known method to improve the symptoms of olfactory dysfunction is ‘olfactory training’ using essential oils. The essential oils used in olfactory training typically include rose, lemon, clove, and eucalyptus, which were selected based on the odor prism hypothesis proposed by Hans Henning in 1916. He classified odors based on six primary categories or dimensions and suggested that any olfactory stimulus fits into his smell prism, a three-dimensional space. The term ‘olfactory training’ has been used based on the concept of training olfactory sensory neurons to relearn and distinguish olfactory stimuli. However, other mechanisms might contribute to how olfactory training can improve the recovery of the olfactory sense. Possibly, the essential oils contain chemical constituents with bioactive properties that facilitate the recovery of the olfactory sense by suppressing inflammation and enhancing regeneration. In this review, we summarize the chemical constituents of the essential oils of rose, lemon, clove, and eucalyptus and raise the possibility that the chemical constituents with bioactive properties are involved in improving the symptoms of olfactory dysfunction. We also propose that other essential oils that contain chemical constituents with anti-inflammatory effects and have binding affinity with SARS-CoV-2 can be new candidates to test their efficiencies in facilitating the recovery.